Americans Deserve to Get a Better Value From CMMI - Louis J. Wilson MD, FACG (SAGE Publishing, 2022)
The CMS Innovation Center was created in section 3021 of the Affordable Care Act (ACA) with the promise to test payment and delivery models expected to reduce costs while improving or maintaining quality of care for Medicare, Medicaid, and Children's Health Insurance Program (CHIP) beneficiaries. Doug Badger's analysis of the Center for Medicare and Medicaid Innovation (CMMI), published in Inquiry, described how the CMMI has failed to accomplish its goals and makes a case for reforms. As a practicing clinician in private practice who has followed the implementation of the components of the Affordable Care Act, including the CMMI, his conclusions are not surprising. An examination of the clinically unworkable and recently delayed Radiation Oncology Alternative Payment Model demonstrates serious flaws in current CMMI methods. Government agencies have difficulty directing innovation. Clinicians know that real innovation will arise in unpredictable ways from the ingenious communities, providers, and organizations that deliver the care. Innovation will occur when an atmosphere of transparency forces providers to respond to the demands of patients. The CMMI would do well to redesign its processes. If "value" is the goal of CMS, then America deserves a better "value" from its healthcare agencies.